Notes on the nomenclature of the genus name Vereia, the earliest-published synonym of Kalanchoe, and the species published in Vereia (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F. (Phytotaxa, 2024)
At the rank of genus, at least seven names have been published for taxa that are today included in Kalanchoe (Crassulaceae subfam. Kalanchooideae). Kalanchoe is the earliest validly published and legitimate name that must be used for the ca. 200 tetramerous-flowered taxa recognised in the genus. Kalanchoe has a wide natural geographical distribution range that stretches from Madagascar and some of the nearby Indian Ocean islands, through most of sub-Saharan Africa and the northern parts of North Africa to the Middle, Near, and Far East, more or less south of the latitude of 35⁰ N. The nomenclature of the genus name Vereia, for which five different spellings have been recorded, is reviewed here. Vereia is the earliest synonym of Kalanchoe. Notes are provided on the natural geographical distribution range of K. crenata, the accepted name of the type, V. crenata, of the genus Vereia. The species names published in Vereia are assigned to species in Kalanchoe.